Reaching a state of hope : refugees, immigrants and the Swedish welfare state 1930 - 2000 - Byström, Mikael 1963- Hrsg; Frohnert, Pär 1956- (Nordic Acad. Press, 2013)
Sweden and the refugees, 1933-45 / Klas Åmark -- A foreign element within the nation / Karin Kvist Geverts -- The politics of Jewish refugee aid and relief work in Sweden / Pontus Rudberg -- Social-democratic solidarity / Pär Frohnert -- The last bastion of Swedish refugee policy / Mikael Byström -- Raoul Wallenberg and Swedish humanitarian policy in Budapest / Paul A. Levine -- Swedish Jews and the Jewish survivors / Malin Thor Tureby -- From contract workers to political refugees / Attila Lajos -- Ethnic encounters, narratives, and counter-narratives / Johan Svanberg -- Controlling the untrustworthy / Cecilia Notini Burch -- Union solidarity in exchange for adaptation / Jesper Johansson -- LO and refugee immigration, 1973-82 / Zeki Yalcin -- Beyond Swedish self-image / Christina Johansson -- The agenda of British refugee policy, 1933-48 / Louise London -- Pre-1945 refugee policy as a reference point for post-1945 policy / Georg Kreis -- Sweden's exceptional ability to organize its immigration / Frank Caestecker